1984
DOI: 10.1177/096032718400300604
|View full text |Cite
|
Sign up to set email alerts
|

Resin Haemoperfusion in Levomepromazine Poisoning: Evaluation of Effect on Plasma Drug and Metabolite Levels

Abstract: 1 Plasma levels of levomepromazine and two of its major metabolites N-desmethyl-levomepromazine and levomepromazine sulphoxide were studied in two poisoned patients treated with resin haemoperfusion at a constant blood flow of 200 ml/min. 2 The mean haemoperfusion clearance of levomepromazine, N-desmethyl-levomepromazine and levomepromazine sulphoxide was 114, 123 and 151 ml/min, respectively, in patient no. 1, and 153, 148 and 184 ml/min, respectively, in patient no. 2. Patient no. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Furthermore, the application of ECTRs, even if they are usually considered generally safe, is not without cost and risks. In the present literature review, adverse effects of ECTRs, other than death, were reported: in subjects undergoing hemoperfusion, thrombocytopenia was reported in 25 patients, anemia in 12, bleeding or coagulation problems in 2, a clotting cartridge in 1, hypotension in 2, hypocalcemia in 5, and pulmonary edema in 1 . Peritoneal dialysis‐related peritonitis was reported in one patient, hyperglycemia in three cases, and hypothermia in one .…”
Section: Recommendationsmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, the application of ECTRs, even if they are usually considered generally safe, is not without cost and risks. In the present literature review, adverse effects of ECTRs, other than death, were reported: in subjects undergoing hemoperfusion, thrombocytopenia was reported in 25 patients, anemia in 12, bleeding or coagulation problems in 2, a clotting cartridge in 1, hypotension in 2, hypocalcemia in 5, and pulmonary edema in 1 . Peritoneal dialysis‐related peritonitis was reported in one patient, hyperglycemia in three cases, and hypothermia in one .…”
Section: Recommendationsmentioning
confidence: 78%
“…From the initial 1312 studies obtained, 77 studies met the inclusion criteria, including 1 observational study , 5 animal studies , 4 in vitro studies , 4 pharmacokinetic (PK) studies , and 63 case reports , 39 of which had sufficient toxicokinetic (TK) data. In total, 108 patients were included for analysis.…”
Section: Resultsmentioning
confidence: 99%